2019
DOI: 10.1111/ajd.13019
|View full text |Cite
|
Sign up to set email alerts
|

Dysplastic/Clark naevus in the era of molecular pathology

Abstract: Dysplastic naevus has been a controversial entity since its first description by Clark in 1978. Despite a recent paradigm shift from the initially proposed notion that dysplastic naevus is a precursor to melanoma, its management has been increasingly more aggressive in the last decade. The latter is due to an unresolved uncertainty regarding its biological nature which necessitates further clarification. Recent molecular genetics, epigenetic and transcriptomic discoveries have revealed that a subset of dysplas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…In conclusion, molecular alterations related to oncogenes, senescence, proliferation and others were described in DN ( 3 ), and in dermoscopically reticular vs globular naevi ( 4 , 8 ). However, the distribution of these or other alterations among the main CAN and DN histopathological and dermoscopic patterns has not been specifically addressed.…”
mentioning
confidence: 76%
See 2 more Smart Citations
“…In conclusion, molecular alterations related to oncogenes, senescence, proliferation and others were described in DN ( 3 ), and in dermoscopically reticular vs globular naevi ( 4 , 8 ). However, the distribution of these or other alterations among the main CAN and DN histopathological and dermoscopic patterns has not been specifically addressed.…”
mentioning
confidence: 76%
“…Regarding other biomarkers, Ki67 and hTERT expression were significantly higher and p16 significantly lower in DN vs IN. Previous studies indicated an increase in proliferation markers and p16 losses in DN and intermediate melanocytic lesions ( 3 , 5 ) and a greater immunoexpression of hTERT in DN than CAN ( 12 ) or, more specifically, in DN vs IN ( 13 ). Moreover, TERT promoter mutations were described as early alterations in inter-mediate lesions ( 5 ).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation